Direito à democracia: uma releitura a partir dos movimentos de protesto de 2011 - Abreu, Mateus Barbosa Gomes (2013)
It is undeniable that the advent of globalization, especially in the last decades of the twentieth century, resulted in several changes in all the States, in a greater or lesser degree, involving even the policy. Among the major changes, there are the formation of a context of porosity among the borders, especially with the advent of computer technology and the Internet, as the need for reconstruction of the idea of sovereignty. In this sense, democracy itself is seen exercised through new instruments, such as the movement of the outraged and other movements that took the streets in 2011, influenced by the “Arab Spring”, and in opposition to the present model of globalization. Thus, considering the complexity of modern society and the particularities of the States, is the existence of a right to democracy possible?